A Comprehensive Analysis of Attenuation Characteristics Using Strong Ground Motion Records for the Central Seismic Gap Himalayan Region, India. Issue 5 (4th April 2022) - Mittal, Himanshu; Sharma, Babita; Chao, Wei-an; Wu, Yih-Min; Lin, Ting-Li; Chingtham, Prasanta
ABSTRACT: This study aims to estimate attenuation characteristics of the central Himalayan region of India concerning various strong-motion parameters such as Kappa value ( κ ) and site effects. We have tried to elaborate on the regional structural heterogeneities and their implications towards the seismic hazard assessment of the study region. A total of 81 earthquakes recorded at 50 stations situated in the central Himalayan region of India are used for the purpose. The particular focus is kept on Kappa value, which shows variability from 0.03 s to 0.095 s, inferring the higher values obtained in plains with deep sediment accumulations proving high-frequency energy dissipation and stiff-soil/rocky sites exhibit comparatively limited attenuation accordingly. To substantiate these results various attenuation parameters such as coda wave quality factor (Qc ), intrinsic attenuation parameter (Qi ), and scattering attenuation parameter (Qs ), have been estimated for two regions in the central seismic gap Himalayan region of India employing the single backscattering model and Wennerberg formulation. The estimated values of Qc, Qi, and Qs are found to be highly dependent on frequency in the frequency range 1.5–24 Hz for both the regions. The average frequency-dependent relationships ( Q = Q 0 f η ) estimated for both regions are Q c = 158 f 1.18 and Q c = 194 f 1.2, respectively. The low value of Q0 shows that the region is highly heterogeneous while the higher value of η indicates higher seismicity in the area. It is also found that intrinsic attenuation is predominant over the scattering attenuation, envisaging the behavior of the wave attenuation through the absorption within the granitic layer at shallow depths. At lower frequencies, Qc values are found close to Qs values, which is in agreement with the theoretical measurements suggesting the presence of complex crustal heterogeneities beneath the region affecting the propagation of seismic waves experiencing considerable decay of energy through scattering. To confirm the aggregate attenuation on the stations, the site characteristics are also determined for examining the behavior of the amplification as the ground motion is comprised of the combined effect of the source, path, and site. The sites are amplified at a predominant frequency ( fpeak ) in between 1.5 to 10 Hz for the central Himalayan region. The different attenuation and amplification parameters like kappa, Q, and site effects can be utilized for detailed seismic hazard analysis (based on ground motion prediction equations) of the area as this region is of great importance from a socio-economic point of view.